Making Peace with Nature - United Nations Environment Programme (United Nations, 2021)
The first UNEP synthesis report presents a scientific blueprint for how climate change, biodiversity loss and pollution can be tackled jointly within the framework of the Sustainable Development Goals. The report serves to translate the current state of scientific knowledge into crisp, clear and digestible facts-based messages that all the world’s citizens can relate to and follow up on. It first provides an Earth diagnosis of current and projected human-induced environmental change, putting facts and interlinkages in perspective with smart infographics. Building on this diagnosis, the report identifies the shifts needed to bridge the gap between current activities and those necessary to achieve sustainable development. Ultimately, the analysis is anchored in current economic, social and ecological realities and framed by economics and the 2030 Agenda for Sustainable Development. By synthesizing the latest scientific findings from a range of recent global environmental assessments, the report communicates the current status of the world’s urgent issues and explores the opportunities to solve them.